A Review on Indicators of Corporate Real Estate Strategies for Hotel Industry in Sri Lanka - Kaluthanthri, P.C.; Osmadi, A. (My University, 2016)
Corporate strategy is a set o f a unique programme designed to achieve specific objectives o f the organization. It describes the philosophy o f the business which executed at departmental level through a functional and tactical plan o f the organization. Many organizations focused on production, marketing, finance and human resources as important functional level priorities and marginal emphasis was given for Corporate Real Estate (CRE); the real estate portfolio o f a nonreal estate organization. However, organizations are required to strategically manage its C R E to unleash the potentiality o f C R E because real estate is a primary factor o f production. The outcome o f the effective and efficient implementation o f the tactical real estate plan is the successful attainment o f organization’s objectives. An effective strategic management o f its CRE is a requirement o f the hotel industry; a subset o f travel and tourism industry o f Sri Lanka to add value to successful attainment o f hotel’s objectives. Therefore effective application o f CR E strategies at the operational level is vital. Since, industry specific tactical level indicators o f CRE strategies are not reviewed at the national context, this study focused to identify tactical level CRE strategic indicators o f the hotel industry in Sri Lanka. Total o f 38 respondents participated in the expert review session that comprised with academic, senior managers o f hotels, management o f the regulatory body o f tourism in Sri Lanka and industry veterans. Lhe Analytic Hierarchy Process (AHP) used as the methodology o f the study to review expert opinion on indicators o f CR E strategies o f the hotel industry in Sri Lanka. Lhe expert panel prioritized 27 CR E strategic indicators o f the hotel industry in Sri Lanka. Lhe finding contributes C R E literature o f hotel industry in Sri Lanka and the study recommends empirical validation o f identified C R E strategic indicators to test the impact o f each indicator on C R E strategy in the hotel industry in Sri Lanka.
Keywords: Strategy; Indicators; Hotel Industry